EFFECTIVE METHODS OF USING DIGITAL APPS LIKE A "PEN PALS" IN TEACHING AND LEARNING ESP AMONG ADULT LEARNERS IN THE WORLD - DILBАR АTKHАMОVNА IBRАGIMОVА; INOBAT FOZILOVNA TUYMANOVA; DILNOZA PARDABOEVNA TOSHPILATOVA (The Bioscan, 2025)
This article aims to provide an in-depth study of the effective use of digital applications such as "pen pals" in the teaching and learning of ESP (English for Specific Purposes) among adult students worldwide. ESP education, unlike traditional English language learning, is focused on developing students' professional needs and language skills in specific areas, and the use of digital applications allows for more interactive, effective and contextual language learning. The article analyzes in detail the main opportunities, advantages and limitations of applications such as "pen pals" in ESP teaching. Through these applications, students develop language skills through written and oral communication, improve intercultural communication and perform tasks tailored to their professional needs. In particular, it creates an opportunity to increase educational efficiency through specially adapted materials and tasks for students in various professional fields (for example, medicine, business, service). Through "Pen Pals" applications, students have the opportunity to use the language in real life, which accelerates their language acquisition process. Although applications increase student motivation, it is shown that there are some technological and cultural barriers. It is analyzed that special tasks in medicine, business, tourism and other fields can be effectively presented through applications. It is emphasized that integration with new technologies such as artificial intelligence, virtual reality (VR) will serve the further development of ESP education. This article is an important guide for ESP teachers and students, which will help to improve the quality of ESP education and adapt it to the needs of students using "Pen Pals" applications. The article offers extensive recommendations for implementing the capabilities of digital applications and educational technologies in practice.